Harvesting energy from human traffic. (24th January 2023) - Johnson, Dazzle; Sayat, Mikhael; Aw, Kean
This brief report investigates a mechanically simple pavement energy harvester using a linear electromagnetic solenoid. This energy harvester will harvest energy from human foot traffic and the design is unique in the sense that it has a very limited vertical displacement of only 1.5 mm and hence minimal effect on the walking gait. This prototype can generate output energy of 164 mW and 833 mW for a single step across a 27 Ω load when a person makes a single step and jump on the pavement respectively. Using a rectifier, the charging of a capacitor with each foot step has been demonstrated. The energy can be increased by having more electromagnetic solenoids.